Entropy‐Aided Evaluation of Meteorological Droughts Over China. Issue 2 (18th January 2018) - Sang, Yan‐Fang; Singh, Vijay P.; Hu, Zengyun; Xie, Ping; Li, Xinxin
Abstract: Evaluation of drought and its spatial distribution is essential to develop mitigation measures. In this study, we employed the entropy index to investigate the spatiotemporal variability of meteorological droughts over China. Entropy values, with a reliable hydrological and geographical basis, are closely related to the months of precipitation deficit and its mean magnitude and can thus represent the physical formation of droughts. The value of entropy index can be roughly classified as <0.35, 0.36–0.90, and >0.90, reflecting high, middle, and low occurrence probabilities of droughts. The accumulated precipitation deficits, based on the standardized precipitation‐evapotranspiration index at the 1, 3, 6, and 12 month scales, consistently increase with entropy decrease, no matter considering the moderately, severely, or extremely dry conditions. Therefore, Northwest China and North China, with smaller entropy values, have higher occurrence probability of droughts than South China, with a break at 38°N latitude. The aggravating droughts in North China and Southwest China over recent decades are represented by the increase in both the occurrence frequency and the magnitude. The entropy, determined by absolute magnitude of the difference between precipitation and potential evapotranspiration, as well as its scatter and skewness characteristics, is easily calculated and can be an effective index for evaluating drought and its spatial distribution. We therefore identified dominant thresholds for entropy values and statistical characteristics of precipitation deficit, which would help evaluate the occurrence probability of droughts worldwide. Key Points: Entropy value is classified as <0.35, 0.36‐0.90, and >0.90, reflecting a high, middle, and low occurrence probability of droughts Northwest and North China, with smaller entropy value, have higher occurrence probability of drought than South China, with a 38°N break The identified entropy thresholds and statistic of precipitation deficit would help evaluate the occurrence probability of drought worldwide